FATIGUE LIFE PREDICTION ON RUBBER JOURNAL COMPONENT MADE IN - FAUZI (NIM : 13106128); Pembimbing: Dr. Ir. Bagus Budiwantoro,; Dr. Andri Andriyana , IMAN
Fatigue failure is a progressive and local structural damage that occurs in materials when subjected to cyclic loading. This leads to the tendency of the material to fracture by means of progressive brittle or crack due to the alternating stress cycle although its below normal strength. Prediction of fatigue failure in the rubber component is an important research to support the needs of the industrial world, especially in Indoneisia, in terms of determining the life of rubber components. In the final project is done the research, namely a simple simulation of rubber components by Ansys 12.1, which is one application program finite element method. This research is a further step of research on uniaxial test stress- strain behavior on the rubber industry of PT. Daya Cipta Indonesia Mandiriinsani, NR Shore 30-35. The test data are used to determine the parameters of hyperelastic model which is one input for the simulation of finite element program. These parameters are the constants of strain energy function (hyperelastic model) on which three hyperelastic model were selected, Neo-Hookean model , Mooney-Rivlin model, and Yeoh model. With the finite element method, it can be determined local stress, local strain of fatigue fracture and life of rubber components subjected to cyclic loading. This research tries to optimize the use of rubber components in Indonesia industry, today. In addition, the fatigue life prediction is a follow-up for rubber supplier to further improve the quality of rubber necessary to conform the industry requirement.